Client-Centered Counseling-Based Resource Center Increased Uptake of HIV Pre-Exposure Prophylaxis (PrEP) in a Randomized Controlled Trial of Young Black Men who have Sex with Men. (4th October 2017) - Desrosiers, Aimee; Zumer, Maria; Levy, Matt; Dright, Aurnell; Jallah, Nikardi; Kuo, Irene; Magnus, Manya; Siegel, Marc
Abstract: Background: New US HIV infections are increasingly concentrated among young Black men who have sex with men (BMSM). Although oral PrEP is recommended by the CDC and WHO, uptake has been low among young BMSM. We evaluated the effect of a resource center offering a client-centered counseling approach to address the psychosocial, health care, and HIV prevention needs of young BMSM on the uptake of PrEP Methods: BMSM aged 16–25 were randomized on a 1:1 basis to (1) standard of care PrEP referral or (2) standard of care PrEP referral + counseling-based PrEP resource center at enrollment with ongoing phone- and texting-based support. Subjects were asked to follow at 3 months. We evaluated the number of subjects who were started on PrEP in the community and the number of new sexually transmitted infections (STIs) over the course of the study Results: 50 HIV- BMSM were enrolled. Median age was 22 years. 43 subjects had seen a doctor in the last 12 months but only 13 had discussed PrEP and only 1 subject had taken PrEP before. 80% of subjects reported unprotected anal sex in the 3 months prior to enrollment, 31% with a man who was HIV-positive or of unknown HIV status. 42 subjects completed the study, 22 in the intervention and 20 in the control arm. 21 subjects saw a medical profession over the study period, of whom 14 discussed PrEp. 6 subjects, all of whom were in the intervention arm, started PrEP and 4 were still taking PrEP at the end of the study ( P = 0.012). At baseline 1 subject was diagnosed with syphilis, 4 with gonorrhea and 10 with Chlamydia. At the 3-month visit, 1 subject was diagnosed with syphilis, 5 with gonorrhea, and 5 with Chlamydia. 2 subjects, 1 in the intervention and 1 in the control arm, tested positive for HIV at the 3-month mark. Neither subject was taking PrEP. There was no difference in the incidence of new STIs between the 2 groups. Fewer subjects reported unprotected anal intercourse both over the study period compared with prior to the study (64% vs. 80%), as well as with men who were HIV-positive or of unknown HIV status (31% vs. 19%) Conclusion: The large number of STIs over the study period (34 STIs in 21 subjects) highlights that this population is at high risk for HIV acquisition and would greatly benefit from PrEP. Our study shows that a resource center is an effective intervention to increase the uptake of PrEP in this patient population Disclosures: All authors: No reported disclosures.